A polgárháború vesztesei a köztársasági menekültek és a köztársasági emigráns kormány - Marosi Ágnes (Belvedere Meridionale Szeged, 2016)
After the coup and the victory of Franco and his supporters nearly half a million of Spanish people had to leave their country and were forced to live in exile. Most of them, who settled in France and Mexico, among other countries, could not return until Franco’s deathin 1975. The republican government existed in exile until 1977 when the Spanish people voted for the restoration of the monarchy. The arrival of Spanish immigrants and their situation in France and Mexico, the difficulties of the adaptation to different conditions and the acceptance of the long exile while preserving the republican idea are important elements of the history of the republican people who left Spain.
Keywords: Bölcsészettudományok; Történettudomány és régészet